Companion Animals as Reservoirs of Multidrug Resistance—A Rare Case of an XDR, NDM-1-Producing Pseudomonas aeruginosa Strain of Feline Origin in Greece - Marios Lysitsas; Eleftherios Triantafillou; Irene Chatzipanagiotidou; Anastasios Triantafillou; Georgia Agorou; Maria Eleni Filippitzi; Antonis Giakountis; George Valiakos (Veterinary Sciences)
A backyard cat with symptoms of otitis was transferred to a veterinary clinic in Central Greece. A sample was obtained and P. aeruginosa was isolated. The strain exhibited an extensively drug-resistant (XDR) profile, as it was non-susceptible to all tested agents except colistin. DNA extraction and whole-genome sequencing (WGS) were performed using a robotic extractor and Ion Torrent technology, respectively. The genome was assembled and screened for resistance and virulence determinants. The isolate belonged to the high-risk clone ST308 with a total of 67 antibiotic resistance genes (ARGs) and 221 virulence factor-related genes being identified. No plasmids were detected. The metallo-beta-lactamase (MBL) blaNDM-1 gene and 46 efflux pumps were included in the strain’s resistome. Both ARGs conferring tolerance to disinfecting agents and biofilm-related genes were identified, associated with the ability of this clone to adapt and persist in healthcare facilities. This case highlights the risk of relevant bacterial clones spreading in the community and even being transmitted to companion animals, causing challenging opportunistic infections to susceptible individuals, while others may become carriers, further spreading the clones to their owners, other animals and the environment.